Implementation of microstepping in stepper motor using ATmega32 microcontroller - Akash, Ishtiaq Hafiz (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.